Comparison of Outcome between Dexamethasone Versus Prednisolone Administration in Acute Moderate Asthma - Nusrat Hussain, Suleman, Asif Javed, Muhammad Yousaf, Nasir, Rabia Saleem Safdar, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To compare the outcome of dexamethasone versus prednisolone administration in acute moderate asthma. Methods: This randomized control trial was carried out in the Department of Pediatrics Nishtar Medical University Multan. The duration of the study was 12 months. 60 (30 in each group) patients were enrolled. Informed consent and demographic detail was taken. Then patients were randomly divided in two groups. In group A, patients were given 5-days course of 1.5 mg/kg/day (max 60 mg) oral prednisolone. In group B, patients were given 2 doses of iv dexamethasone (0.6 mg/kg/dose) 24 hours apart. During hospital stay, children were evaluated for cough, wheezing and vomiting. When symptoms were resolved, then children were discharged and total hospital stay was noted. Results: In this study, in oral prednisolone group, the mean hospital stay of1the patients was 28.9±7.99 hours and in IV dexamethasone group the meanhospital stay was 24.2±6.08 hours (p-value=0.013). In oral prednisolone group, the readmission within 7 days was found in 10(33.3%) patients and in IV dexamethasone group the readmission within 7 days was 3(10%) patients (p-value=0.028). In oral prednisolone group, the vomiting was noted in 6(20%) patients and in IV dexamethasone group the vomiting was noted in 3(10%) patients (p-value=0.472). In oral prednisolone group, the cough was noted in 16 (53.3%) patients and in IV dexamethasone group the cough was noted in 8(26.7%) patients (p value=0.035). In the oral prednisolone group the wheezing was noted in15 (50%) patients and in IV dexamethasone group wheezing was noted in 7(23.3%) patients. Conclusion: IV dexamethasone showed statistically significant better outcome in terms of wheezing, cough, shorter hospital stay and readmission within 7 days as compared to oral prednisolone administration in acute moderate asthma. Key words: Acute asthma, Dexamethasone, Prednisolone